Olmesartan-Induced Enteropathy: A Rare Case of Chronic Diarrhea - Sofia Emerenciano Gurgel; Kleyton Santos de Medeiros; Sarah Jane Lima de Paiva; José Gurgel Filho (Case Reports in Medicine)
The case involves a 63-year-old hypertensive man, taking antihypertensive medication (olmesartan) for the previous two years, who sought medical attention due to voluminous diarrhea, with several episodes per day and weight loss of 10 kg. He was submitted to a series of diagnostic procedures without elucidation and empirical treatment with unsuccessful outcome. After hospitalization for clinical stabilization and for presenting with duodenal atrophy, obtained by duodenal biopsy associated with negative markers for celiac disease, the patient was diagnosed with suspected olmesartan-induced enteropathy, showing rapid improvement of diarrhea after the drug was withdrawn, with weight regain in 6 months and normalization of the duodenal histological picture after 10 months.